Knowledge creation, diffusion, and use in innovation networks and knowledge clusters : a comparative systems approach across the United States, Europe, and Asia - Carayannis, Elias G.; Campbell, David F. J., 1963- (Technology, innovation, and knowledge management., 2006)
In the 21st century, intangible resources such as knowledge and social capital have become as necessary to the modern economy as coal, diamonds, and oil were to the past. This shift from product-focused to service-focused economies necessitates a drastic re-thinking of the ways in which we support the mission and business of economic development on a global, regional, and national scale. In order to effect and sustain a positive change, innovation and knowledge networks need to be connected to every aspect of life, from the private and domestic, to the corporate and the global. This book integ.